Overt Thyroid Dysfunction During Treatment of Hepatitis C Patients with Interferon and Ribavirin (Medical Forum Monthly, 2024)
Objective: To find out the thyroid dysfunctions during treatment hepatitis C patients with Interferon and Ribavirin.Study Design: Observational / descriptive studyPlace and Duration of Study: This study was carried out at the Teaching Hospital, Ghazi Khan Medical College, DG Khan from April 2015 to January 2016.Patients and Methods: Fifty patients of chronic HCV were enrolled.Results: Out of 50 treated patients 35 were female and 15 were male. Fifteen (15%) patients developed thyroid dysfunction and out of these 15 patients (11 female [73.3%] and 4 male [26.7%]).Ten (66.6%) out of 15 patients developed hypothyroidism and 5(33.3%) out of 15 patients developed hyperthyroidism. Seven (70%) out of 10 patients who developed hypothyroidism needed levothyroxine therapy. Two (40%) out of 5 patients who developed hyperthyroidism needed carbimazol therapy for their symptoms and disease control. All patients completed hepatitis C treatment with combined Peg-Interferon Alpha-2a and Ribavirin therapy.Conclusion: The involvement between thyroid dysfunction in hepatitis C individuals and management with IFN-alpha and RIBA.